2018
DOI: 10.1002/mnfr.201800729
|View full text |Cite
|
Sign up to set email alerts
|

High‐Saturated Fat High‐Sugar Diet Accelerates Left‐Ventricular Dysfunction Faster than High‐Saturated Fat Diet Alone via Increasing Oxidative Stress and Apoptosis in Obese‐Insulin Resistant Rats

Abstract: Scope It has been hypothesized that a high‐saturated‐fat, high‐sugar diet (HFHS) causes worse cardiometabolic dysfunction than a high‐saturated‐fat diet (HFD) due to severe mitochondrial dysfunction, oxidative stress, and apoptosis in obese insulin‐resistant rats. Methods and Results Rats are divided into three groups to receive normal diet (ND), HFD, or HFHS for 24 weeks. Cardiometabolic parameters are determined at baseline and every 4 weeks until the end of the feeding protocol. At week 24, hearts are remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
(104 reference statements)
4
20
1
Order By: Relevance
“…Oxidative stress is a very vital contributor to HFD-induced myocardial lipotoxicity. Previous studies show that excessive lipid accumulation triggered by HFD feeding could cause increased oxidative stress and subsequent apoptosis of cardiomyocytes 1,33. Consistent with these observations, we demonstrated that the levels of ROS were higher in palmitate-stimulated NRCMs and DIO heart.…”
supporting
confidence: 91%
“…Oxidative stress is a very vital contributor to HFD-induced myocardial lipotoxicity. Previous studies show that excessive lipid accumulation triggered by HFD feeding could cause increased oxidative stress and subsequent apoptosis of cardiomyocytes 1,33. Consistent with these observations, we demonstrated that the levels of ROS were higher in palmitate-stimulated NRCMs and DIO heart.…”
supporting
confidence: 91%
“…Prolonged severe obesity may result in left ventricular (LV) dilation, increased LV wall stress, compensatory LV hypertrophy, myocardial fibrosis and LV diastolic dysfunction with progression to systolic dysfunction if wall stress remains high . The high‐fat diet (HFD) is known to be a major cause of obesity, and the HFD is used to induce cardiometabolic dysfunction and for investigation of the mechanisms responsible for metabolic heart disease . The overload of nutrients impairs cardiac mitochondrial function, leading to decreased mitochondrial biogenesis, reduced mitochondrial coupling efficiency and decreased ATP synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Mice fed a HFD have increased DRP1‐dependent mitochondrial fission which is linked to increased oxidative stress, decreased ATP production, insulin resistance and cardiac dysfunction . Rats fed a HFD have cardiometabolic dysfunction, myocardial mitochondrial dysfunction and impairment of mitochondrial dynamics; the HFD not only downregulates mitochondrial fusion‐related proteins but also upregulates fission‐related proteins …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations